Potential of Africa for Automotive - Oshchebska, Sofiya; Křečková Kroupová, Zuzana, 1972-; Průša, Přemysl, 1980-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
This thesis is dedicated to the estimation of the potential of African continent for the automotive market entry. The work starts with the introduction of key internationalization, market assessment and market entry theories. Author then conducts a general analysis of automotive industry and evaluates the competitive forces that are shaping it nowadays. The research continues with the identification and evaluation of key drivers of Africa's future growth. Final practical part of the thesis is presented in the form of comparative study of four African countries: Egypt, Morocco, South Africa and Tunisia, that according to the author present the highest market potential for automotive in Africa. Country comparison and ranking is conducted by the application of PESTLE framework. In the end Egypt is identified as a preferred country and a list of recommendations on the automotive market entry strategy for Egypt is provided.
Vedoucí práce: Zuzana Křečková Kroupová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses